Aktivitas Antijamur Ekstrak Kecombrang (Etlingera elatior) Terhadap Aspergillus Flavus FNCC 6109 - Rizky Nasution, Yovanda; Selamet Duniaji, Agus; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p03, 2020)
The aim of this research was to determine the concentration of phenol compounds and antifungal activity of torch ginger (Etlingera elatior) on Aspergillus flavus FNCC 6109. This research was a completely randomized design with 10 concentrations of shoot, flower, and fruit extract which were 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. The data were analyzed with variance analysis then followed by Duncan Multiple Range Test (DMRT). Analysis were repeated 2 times resulting in 20 experimental units. Result showed that each concentration of shoot, flower, and fruit extract had significantly effect (P<0,05) in inhibition of Aspergillus flavus FNCC 6109. Shoot, flower, and fruit extract of torch ginger contained phenol compounds of 154,56 mgGAE/g, 127,22 mgGAE/g, and 261,52 mgGAE/g. The best antifungal activity for shoot extract of torch ginger was at 70% concentration with a diameter inhibition of 7,9 mm category medium, for flower extract of torch ginger was at 90% concentration with a diameter inhibition of 5,65 mm category medium, and for fruit extract of torch ginger was at 80% concentration with a diameter inhibition of 13,75 mm category strong. Fruit extract of torch ginger had the highest phenol compound which could inhibit Aspergillus flavus FNCC 6109. Keywords : phenol, torch ginger, antifungal, Aspergillus flavus.